India@2047: Future tech HRM and The Startup Innovation Agenda - Kshitija T Kanagale; G.R. Junnaykar (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
The emergence of a technology-driven economy has transformed how organizations manage people and innovation. Startups, often referred to as the engines of disruption, are adopting advanced technologies to redefine traditional Human Resource Management. This paper explores the concept of FutureTech HRM, where digital tools such as artificial intelligence, people analytics, and blockchain are integrated with HR practices to drive people-centric innovation. With India’s vision of becoming a global innovation hub by 2047, the study emphasizes the significance of startups leveraging FutureTech Human Resource Management to balance automation with human values, enabling inclusive growth, enhanced performance, and sustainable competitiveness. Through a mixed-method approach combining secondary research, case study analysis, and a proposed survey design, the study highlights the role of HRM as a strategic enabler of innovation in startups. The findings suggest that FutureTech HRM is not only crucial for organizational success but also essential for building resilient, human-centered work ecosystems in the digital economy.